Avaliação preliminar do potencial de implantação de sistemas híbridos de energia sustentável na UFSCar: integração entre biogás e energia fotovoltaica - Santos, Julia dos (Universidade Federal de São Carlos, 2025)
Considering the intensification of the impacts caused by climate change and the consequent demand for sustainable energy solutions, it becomes imperative for public institutions, particularly universities, to adopt practices aimed at mitigating their environmental impacts. Public universities, due to their extensive infrastructure, high energy consumption, and academic and social influence, are strategic environments for the implementation of renewable energy generation systems. In this context, the present Undergraduate Thesis aims to preliminarily analyze, through a literature review, the implementation of a hybrid energy generation system on the São Carlos campus of the Federal University of São Carlos (UFSCar), integrating photovoltaic solar energy and biogas produced from the utilization of organic waste from the university restaurant (RU) and plant prunings. The methodology adopted consisted of the research and analysis of national and international scientific literature, covering studies on both technologies individually, as well as their applications in hybrid systems. The data obtained were compared with the current energy scenario of the campus, enabling the identification of critical variables and the proposal of strategies to optimize energy generation. The results highlight the potential of integrating these renewable sources as a viable and sustainable alternative for the university context, contributing to the reduction of dependence on non-renewable sources and promoting institutional energy efficiency.
Preliminary assessment of the potential for implementing hybrid sustainable energy systems at UFSCar: integration between biogas and photovoltaic energy.
Keywords: sistema híbrido de energia; energia fotovoltaica; biogás; universidade; hybrid energy systems; photovoltaic energy; biogas; university; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; 7. Energia limpa e acessível; 9. Indústria, Inovação e Infraestrutura; 13. Ação contra a Mudança Global do Clima